Heejab International Sdn Bhd / Farahin Hannani Mohd Nordin - Mohd Nordin, Farahin Hannani (Faculty of Business and Management, 2023)
This report is about the task that has been worked on during the internship. Six months of industrial training began at Heejab International Sdn Bhd starting 1st of March 2023 until 15th of August 2023. This report presents the content of the student’s resume, company background, vision, mission, goals, organizational structure of a company and product. There are also SWOT analysis of Heejab International Sdn Bhd included in this content of report. The scope of this report is to identify a SWOT analysis that has been applied in industrial training during six months based on job tasks completed, a task has been learned, the experience that has been gained, and the student’s achievement during industrial training under Marketing department in Heejab. The trainee we are introduced to the system that has been used, terms of procedures, and the most important was work culture and work environment. There was also the suggestion or recommendation for strength, weaknesses, opportunities and threats. The trainee discovers how to overcome those problem. Communication, problem-solving skills, and also management skills are applied based on the practical knowledge of student internship. After the internship, the trainee gained more knowledge of working behaviour, practiced in the working environment, and have a depth understanding of how to work in a company.